Design an ultra-wideband modified wilkinson power divider fed-by balanced antipodal vivaldi antenna array for imaging applications - Shaikh, Faraz Ahmed; Khan, Sheroz; Zahirul Alam, A. H. M.; Habaebi, Mohamed Hadi; Baillargeat, Dominique (Universiti Teknikal Malaysia Melaka, 2020)
In this paper, design of compact and modified geometrical structure of 1-to-4 way ultra-wideband Wilkinson power divider used as a feeding network for 4-element of balanced antipodal Vivaldi antenna (BAVA) array has introduced. The proposed Wilkinson power divider has been designed and printed on low-cost Epoxy laminate substrate FR4 along with the thickness of 1.6mm and relative permittivity of ɛr =4.3 respectively. The transformation of power divider network which are based on bent corners as a replacement of sharp corners or edges used for the decrement in unintended radiation and employing a single radial stub on each branch to encounter the antenna-specifications. Further some adjustments in the dimension of stubs matching in order to increase the reflection of the power divider network. The design presents the model of a power divider and maintains an equal power splitting at different ports with practical insertion loss and conventional return loss below -10dB. The reasonable impedance matching has achieved at every single port with acceptable isolation performance values over the (3-to-10 GHz) frequency range. The divider as well as antenna elements design and its optimization are practicable via computer simulation technology (CST) simulation software. The experimental results are revealed to encounter the array-specifications under ultra-wideband frequency range .